PENGGUNAAN MEDIA PEMBELAJARAN QUIZIZZ DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP WAHID HASYIM MALANG - Alifah Nurul Irfani; Ika Ratih Sulistiani; Arief Ardiansyah (VICRATINA, 2021)
Quizizz media is one of the learning media that can help students become more active and not boring. SMP Wahid Hasyim is one of the schools that implements learning using quizizz media. This study aims to determine the implementation of quizizz media in PAI subjects at SMP Wahid Hasyim, to find out the obstacles, and to resolve obstacles in the use of Quizizz media in PAI subjects at SMP Wahid Hasyim. This study uses a qualitative method, the data sources in this study are secondary and primary. The use of quizizz learning media in PAI subjects at SMP Wahid Hasyim Malang has been going well. Supporting factors in this research are adequate facilities and infrastructure. The inhibiting factor in the use of Quizizz learning media in PAI subjects at SMP Wahid Hasyim Malang is the signal limitation.